Aspectos biológicos, predação e resposta funcional de euborellia annulipes (Lucas) (Dermaptera: Anisolabididae) tendo plutella xylostella (L.) (Lepidoptera: Plutellidae) como presa - Nunes, Gilmar da Silva (2017)
This work aimed to characterize some biological aspects and to evaluate predatory behavior and functional responses of E. annulipes preying larvae and pupae of Plutella xylostella. Besides, it was aimed to compare the efficiency of statistical methods (Bootstrap and Marquadt) to stimate functional response parameters, a e Th. The experiments were conducted under laboratory conditions. Initially, we evaluated nymphal development, predator weight, fecundity, fertility, longevity, and survival probability of E. annulipes males and females with P. xylostella larvae at first + second, third, and fourth instars, and P. xylostella pupae with one, two and three days old. Predatory behavior of E. annulipes having P. xylostella larvae and pupae as prey were assessed, and the number of insects preyed per day as function of prey stage and predator age (2, 4, 6, 8 and 10 days) were recorded. The prey stage preference, weight gain and functional responses of predator as function of prey densities (30, 40, 50, 60 and 70 larvae; 5, 10, 15, 20 and 25 pupae) were analysed. E. annulipes nymphs presented shorter development period when fed on P. xylostella fourth instar larvae, the weight of nymphs and adult was higher when the ring-legged earwig fed on pupae of three days old, adult stage longevity and survival probability were not mediated by the food consumed, and earwig fertility was only checked in the feeding with pupae. The movements of P. xylostella larvae incite the predation and pupae are less consumed by nymphs, from the third instar, and E. annulipes females. In the second, third and fifth instars the consumption of larvae presented quadratic responses, and predator females consume these preys linearly. Pupae are consumed linearly from two to 10 days old by nymphs in the second, fifth instars and females, but are less consumed in relation to larvae by the predator from their third instar. There is greater preference of E. annulipes for P. xylostella larvae in relation to pupae. The functional response of the earwig is type II for each prey stage, and Bootstrap method has more precise efficiency for predicting attack rate and handling time parameters of E. annulipes on P. xylostella.